E-Faktur Dan Pelaporan SPT Masa Pajak Pertambahan Nilai - Meilinda Stefani Harefa; Nelta Suryatna Putri Bu’ulolo; Vebry Lumban Gaol (Visi Sosial Humaniora, 2023)
The purpose of this study is to know the application of e-Tax Invoice in the filling and reporting of Periodic Tax Return Value Added Tax CV ABC. This research is qualitative descriptive data research and uses primary data that is obtained or collected directly in the field by researchers from the person concerned. The data collection methods used are literature studies, observation and documentation. CV ABC is a company that operates in the field of sales and purchase of spare parts and one of the clients of Eben Ezer Simamora Tax Consultancy Office. From the results of the research, it can be concluded that the filling of Periodic Tax Return Value Added Tax using the e-Tax Invoice application has been implemented in accordance with the applicable regulations, namely the regulations of the Directorate General of Taxes Number PER-16/PJ/2014 with rates 11% with the rates regulated in Law No. 7 of 2021 regarding Harmonization of Tax Regulations and performed the obligation to report Periodic Tax Return Value Added Tax in a timely manner so that it was never subjected to a reporting delay sanction and has been in conformity with the legislative regulations No.42 Year 2009 Article 15A and PMK No.242/PMK.03/2014.